Estágios Evolutivos da Contabilidade Gerencial e Desempenho: estudo em empresas brasileiras do agronegócio - Silva, Caroline Maria da (2023)
The objective of this study is to empirically test the sequencing between the evolutionary stages of management accounting and the relationship between more advanced evolutionary stages and performance in the largest agribusiness companies. The study data, quantitative and descriptive in nature, were collected via survey with 165 valid responses from large agribusiness companies. For data treatment and analysis, descriptive statistics and the Multinomial Logit (MNL) method were used. The findings point out that, in fact, there is a sequencing in the evolutionary stages of management accounting as pointed out by the theory and that, although most organizations are classified as belonging to the fourth evolutionary stage of Management Accounting, the best perceived performances were seen by second-stage organizations. Thus, it is relevant to highlight that, despite the good overall performance of the sector, companies categorized in higher evolutionary stages in terms of management accounting practices did not stand out in relation to the others. It is important to note the second stage practices, Product Profitability Analysis, Break-even Point, Contribution Margin, Cash Flow, and Budget, as practices more evident in the best performing agribusiness companies. The research empirically tests the evolution in stages of management accounting practices in Brazilian agribusiness companies, highlighting factors that differentiate them in relation to performance, demonstrating the particularities among the evolutionary stages in which they are inserted. Furthermore, it highlights management accounting practices that would be related to better performance in the sector.